2022
DOI: 10.3390/su14106330
|View full text |Cite
|
Sign up to set email alerts
|

Application of Tree-Based Ensemble Models to Landslide Susceptibility Mapping: A Comparative Study

Abstract: Ensemble machine learning methods have been widely used for modeling landslide susceptibility, but there has been no uniform ensemble method for this problem. The main objective of this study is to compare popular ensemble machine learning-based models and apply them to landslides susceptibility mapping. The selected models include the random forest (RF), which is a typical bagging ensemble model, and three advanced boosting models, namely, adaptive boosting (AB), gradient boosting decision trees (GBDT), and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…The quantitative results show that the order of the AUC values from small to large is RF model > XGBoost model > gcForest model. Additionally, the findings agree with those of Wei et al, who reported that the prediction accuracy of an XGBoost model was higher than that of an RF model [ 32 ]. The accuracy, AUC value, recall rate, test set precision, and kappa coefficient of the gcForest model with stacking were 0.958, 0.991, 0.965, 0.946, and 0.91, respectively, which are significantly better than the values of the other two models.…”
Section: Discussionsupporting
confidence: 91%
“…The quantitative results show that the order of the AUC values from small to large is RF model > XGBoost model > gcForest model. Additionally, the findings agree with those of Wei et al, who reported that the prediction accuracy of an XGBoost model was higher than that of an RF model [ 32 ]. The accuracy, AUC value, recall rate, test set precision, and kappa coefficient of the gcForest model with stacking were 0.958, 0.991, 0.965, 0.946, and 0.91, respectively, which are significantly better than the values of the other two models.…”
Section: Discussionsupporting
confidence: 91%
“…Conditioning factors selection is a fundamental step for an adequate LSM generation. In this research, the selection of factors was based mainly on the availability of information in the study area, and it is important to point out that there is no selection standard, since each study area has different characteristics [42]. In this sense, information on 15 landslide conditioning factors was available: topographic (10): elevation, slope, slope aspect, curvature, stream power index (SPI), sediment transport index (STI), topographic position index (TPI), terrain ruggedness index (TRI), topographic wetness index (TWI), and solar radiation index; land cover (3): land cover, distance to roads, and normalized difference vegetation index (NDVI); hydrological (1): distance to rivers; and geological (1): lithology.…”
Section: Conditioning Factorsmentioning
confidence: 99%
“…Kavzoglu and Teke [6] analyzed the performance of different ensemble ML predictive algorithms in Macka County (Turkey) and confirmed the superiority of NGBoost. Wei et al [42] carried out a comparative study of tree based ensemble models for LSM in Laiyuan County (China) and found that XGBoost and RF obtained the best performance. Badola et al [43] conducted a landslide susceptibility analysis using XGBoost in the Chamoli district (India) and obtained a satisfactory performance.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of a highway landslide disaster is closely related to topography, geological structure, hydrometeorology and human activities, and selecting suitable evaluation factors is the most important part of a landslide susceptibility evaluation, but due to the complexity of the influencing factors, there is no unified selection standard yet [27,28]. A highway, as a typical line-fitting engineering structure, has to traverse different topographic and geomorphological units, especially in mountainous areas, often spreading over slopes, valleys and mountain ranges.…”
Section: Selection Of Evaluation Factorsmentioning
confidence: 99%